Decompensation of chronic open-angle glaucoma following mydriasis-induced pigmentary dispersion into the aqueous humour: a light and electron microscopic study. Issue 4 (April 1981) - Haddad, R; Strasser, G; Heilig, P; Jurecka, W
Abstract : A patient with well controlled chronic open-angle glaucoma developed after dilatation of both pupils persistent increase in intraocular pressure (IOP) due to extensive pigmentary dispersion into the aqueous humour. Trabeculectomy specimens obtained from both eyes after 3 and 7 weeks were studied by light and electron microscopy. It seems evident that the initial phase of raised IOP was caused by a clogging mechanism to the outflow channels by melanin and phagocytic cells. The permanent increase in IOP is attributed to the damage induced in the fibrous components of the trabecular sheets as a result of a complete breakdown of their endothelial covering.